Ta’ṡiir istikhdām Padlet ‘Alā Natiijat At Ta’allum Al Lugah Al ‘Arabiyyah - Wardahni, Nisrina Akifah (Universitas Islam Negeri Imam bonjol Padang, 2024)
The teaching of Arabic language in schools does not vary in the use of media. This study aims to determine the influence of the use of learning media on Arabic language learning outcomes and to provide a reference for the use of Padlet media to educators. This research employs a quantitative approach with a quasi-experimental design using a post-test only group design. The sample in this study consists of students from SMP Muhammadiyah 31 Jakarta, with 29 students from class VIII C as the control group and 32 students from class VIII A as the experimental group. The instrument used in this study is a test instrument in the form of a multiple-choice post-test consisting of 40 questions. The testing of the instrument was conducted using Microsoft Excel and SPSS version 29. The results of this study indicate that there is an influence of the use of Padlet media on Arabic language learning outcomes in the experimental class, with a t-test result showing t-count 2.093 t-table 1.670. The use of Padlet media affects the Arabic language learning outcomes of students.